Faces of change social work in the new millennium - Tower, Kristine; Ussher, Jodi.; Council on Social Work Education (New York : Distributed by Insight Media, 2000)
This video is an introduction to social work and its many areas of practice. Viewers will find social workers in their different environments talking about the work they do and confronting negative myths about the profession.
DVD.
Originally produced in 1997.
Executive producer, Kristine Tower ; producer, Jodi Ussher Lewis.
Narrators, Susan Chandler, Tom Nelson.
"This video was created by the students of Dr. Kris Tower and Dr. Susan Chandler in their class 'Social work and the media.'"
Keywords: Social work education -- United States; Social workers -- United States; Social service -- Vocational guidance -- United States